İşçinin iş sözleşmesini 4857 sayılı kanun uyarınca haklı nedenle feshi - Peken, Talanur (My University, 2020)
İşçinin işverene bağımlı olarak iş görmeyi, işverenin ise ücret ödemeyi üstlendiği sözleşme, iş sözleşmesi olarak adlandırılmaktadır. İş sözleşmesi, sürekli borç ilişkisi doğuran bir sözleşmedir. Ancak bu durum iş sözleşmesinin süresiz olduğu veya sona erdirilemeyeceği anlamına gelmemektedir. İş sözleşmesi çeşitli sebeplerle sona erebilir. Bu sebeplerin başında iş sözleşmesinin feshi gelmektedir. İş sözleşmesinin feshi ise haklı nedenle fesih ya da süreli fesih şeklinde yapılabilir. Haklı nedenle fesih hakkı hem işverene hem işçiye tanınmış bir haktır. 4857 sayılı Kanun’da işçi bakımından haklı nedenle fesih hakkı 24. maddede ele alınmıştır. İşçinin iş sözleşmesini haklı nedenle fesih hakkı sonuçları bakımından işçi ve işveren açısından büyük önem taşımaktadır. Bu çalışmada da işçi tarafından iş sözleşmesinin 4857 sayılı Kanun uyarınca haklı nedenle fesih halleri Yargıtay tarafından verilen karar örnekleri ile birlikte işlenerek ele alınmıştır.

The contract in which the worker undertakes to work as a dependent employee and in return, the employer undertakes to pay salary, is called an employment contract. As can be understood from this definition, the employment contract creates a constant debt relationship. However, this does not mean that the employment contract is concluded for an indefinite term or it can not be terminated. The employment contract may terminate for various reasons: One of them is the termination of the employment contract. Termination of the employment contract can be made via just cause, or regular termination (by abiding the relevant termination notice periods indicated in the legislation). Both the employer and the employee have been entitled with the right to termination for a just cause. In the Law No. 4857, the right of termination for just cause granted for the employees are referred to in Article 24. The right of the employee to terminate the employment contract with just cause is therefore of great importance for both the employer and the employee in terms of its consequences. In this study, the termination of the employment contract by the worker for a just cause in accordance with Law No. 4857 is evaluated and elaborated with relevant examples from the decisions given by the Supreme Court
Keywords: Civil law; employee rights; Haklı nedenle fesih hakkı; iş sözleşmesinin feshi; işçinin hakları Right to termination for a just cause; Medeni hukuk; the employment contract